Paroxysmal Kinesigenic Dyskinesia as the Presenting and Only Manifestation of Multiple Sclerosis after Eighteen Months of Follow-Up - Marius Baguma; Michel Ossemann (Journal of Movement Disorders, 2017)
Other than tremor, movement disorders are uncommon in multiple sclerosis. Among these uncommon clinical manifestations, paroxysmal kinesigenic dyskinesia is the most frequently reported. It is characterized by episodic attacks of involuntary movements that are induced by repetitive or sudden movements, startling noise or hyperventilation. The diagnosis is essentially clinical and based on a good observation of the attacks. It is very easy to misdiagnose it. We describe the case of a young female patient who presented paroxysmal kinesigenic dyskinesia as the first and only clinical manifestation of multiple sclerosis, with no recurrence of attacks nor any other neurologic symptom after eighteen months of follow-up.